Oncologic reconstruction of the hand and upper extremity: Maximizing functional outcomes. Issue 8 (June 2016) - Knaus, William J.; Alluri, Ram; Bakri, Karim; Iorio, Matthew L.
Abstract : Upper extremity malignancies have the potential to create significant functional impairment, and as such represent an opportunity for collaborative reconstruction to minimize potential morbidity. Given the increased complexity and array of potential reconstruction solutions, functional limb preservation is overwhelmingly and increasingly successful in appropriately selected patients. The purpose of this review is to familiarize the reader with the general functional considerations of the upper extremity, review major reconstructive options, and present a general algorithm for reconstruction and maintenance of function. J. Surg. Oncol. 2016;113:946–954 . © 2016 Wiley Periodicals, Inc.